Big stories about big squids: The story of the Britannia and the birth of a wartime urban legend. (July 2021) - Dyer, Jonathan
A popular urban legend from World War II involves the survivors of a sunken British troopship being attacked by a giant squid. The story of R.E.G. Cox and the giant squid he claimed that attacked him can be found in a wide variety of written and online sources. This article explores the origins of this urban legend, looks at its spread, and debunks it through both historiographical research and a brief scientific examination of relevant marine life.